ARXAIK EPOSNING SUJET STRUKTURASIDA MOTIVLAR TAHLILI - Sharipova Maxbuba Baxshilloyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article highlights the relationship between epic and ritual, ethnicity and epic in the Uzbek epic according to the socio-historical, cultural and spiritual foundations, its antiquity, traditionality and the scientific and theoretical foundations of ethnology.